1988
DOI: 10.1152/jn.1988.59.2.450
|View full text |Cite
|
Sign up to set email alerts
|

Slow conductances in neurons from cat sensorimotor cortex in vitro and their role in slow excitability changes

Abstract: 1. The electrophysiological and pharmacological properties of slow afterpotentials in large layer V neurons from cat sensorimotor cortex were studied in an in vitro slice preparation using intracellular recording and single-microelectrode voltage clamp. These properties were used to assess the role of afterpotential mechanisms in prolonged excitability changes. 2. The mean duration of a slow afterhyperpolarization (sAHP) was 13.5 s following 100 spikes evoked at 100 Hz. Its time course was best described by tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
219
1
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(233 citation statements)
references
References 0 publications
11
219
1
2
Order By: Relevance
“…Slow spike-frequency adaptation in these cells results in large part from spike-triggered Ca 2ϩ -and Na ϩ -dependent K ϩ conductances that cause a sAHP after repetitive spiking (Madison and Nicoll, 1984;Schwindt et al, 1988Schwindt et al, , 1989. We found that slow adaptation and the sAHP were prominent in most layer 2/3 cells ( Fig.…”
Section: E)mentioning
confidence: 70%
See 1 more Smart Citation
“…Slow spike-frequency adaptation in these cells results in large part from spike-triggered Ca 2ϩ -and Na ϩ -dependent K ϩ conductances that cause a sAHP after repetitive spiking (Madison and Nicoll, 1984;Schwindt et al, 1988Schwindt et al, , 1989. We found that slow adaptation and the sAHP were prominent in most layer 2/3 cells ( Fig.…”
Section: E)mentioning
confidence: 70%
“…This compound was previously shown to reduce the sAHP (Villalobos et al, 2005) and increase gain (Zhang and Arsenault, 2005), actions shared with several neuromodulators including serotonin, acetylcholine, and norepinephrine (Schwindt et al, 1988Foehring et al, 1989;Lorenzon and Foehring, 1993;Cox et al, 1994;Spain, 1994). To prevent any effects attributable to altered synaptic activity, the control recording solution for these experiments contained DNQX (20 M), CPP (5 M), and picrotoxin (100 M) to block AMPA/kainate, NMDA, and GABA A receptors, respectively.…”
Section: E)mentioning
confidence: 99%
“…Muscarine bas also been linked to a slow afterdepolarization of neurons, which enhances excitability by extending membrane depolarization (McCormick & Prince, 1986;Schwindt et al, 1988). In lB neurons, muscarinic receptor activation bas been shown to produce depolarization~y suppressing both a voltageindependent and a voltage-dependent 1(+ current (Wang and McCormick, 1993).…”
Section: Pyramidal Neuronsmentioning
confidence: 99%
“…To understand how such variability affects the encoding of the extrinsic directional signal, we must first address the intrinsic biophysical properties of neurons. The ionic nature of different types of conductance has been well-established for cortical and thalamic neurons (Crill, 1996;Llinas, 1988;Schwindt et al, 1988a;Schwindt et al, 1988b). Generally speaking, the spiking properties of thalamic neurons range from tonic or regular firing to bursting or phasic (Steriade, 2001).…”
mentioning
confidence: 99%